Optimalisasi Bagi Hasil pada Akad Musyarakah - Thahirah, Afifah; Halim, Abdul (Nagari Law Review, 2023)
Financing people's businesses from Sharia banks is essential in supporting the development of small and medium enterprises and promoting Islamic economic principles based on justice and sustainability. So, from this problem, the problem formulation can be taken as follows: How to Optimize Profit Sharing in Musyarakah Contracts. The research method used is normative law, namely a legal research method that places law as a building system of norms. The data analysis technique uses qualitative methods, namely descriptive research, which tends to use analysis. Two methods can be used to optimize the calculation of the profit-sharing ratio in Musyarakah. They are profit-sharing and revenue-sharing. Profit sharing is the distribution of investment results based on the net profit obtained from the business. In contrast, revenue sharing is the distribution of investment results based on the gross income received from the business. The method chosen must be adjusted to the agreement between the Musyarakah partners and the business's conditions. Optimizing profit sharing aims to ensure that each party shares responsibility and risk fairly, according to their respective capital contributions and participation.